Immobilization of the Highly Dispersed Fullerene on the Surface of Cyclodextrin Modified Layered Double Hydroxides Film - Lei Liu, Xiao; Wang, Qian; Guo Geng, Dian; Wei, Min; Duan, Xue (Asian Journal of Chemistry, 2011)
A novel method was studied for the immobilization of the fullerene on the surface of cyclodextrin modified layered double hydroxides film. The supramolecular structure, physico-chemical behaviour and thermal decomposition were characterized by XRD, UV-VIS, NMR and TGDTA. The XRD results show that the basal spacing of the resulting C60/CMCD-LDH film is similar with that of the CMCD-LDH film. Moreover, the UV-VIS result indicates the interaction between C60 with inclusion host-CMCD, which confirmed the fullerene was only included by the CMCD on the surface of LDH. The thermal decomposition of C60/CMCD-LDH was also investigated by TG-DTA measurements. Compared with the pure fullerene, the thermal stability of C60/CMCD-LDH is reduced after highly dispersed and its combustion temperature decreased by 100 ºC. Therefore, this work provides a novel dispersed fullerene based on functionalized CD/layered material composite. Furthermore, the schematic model of the inclusion structure has been proposed. Further investigation will focus on the photoelectrochemical and optical limiting properties of these fullerene-trapped layered double hydroxide materials.